Assignment of the tibial muscular dystrophy locus to chromosome 2q31. - Haravuori, H (1998)
Tibial muscular dystrophy (TMD) is a rare autosomal dominant distal myopathy with late adult onset. The phenotype is relatively mild: muscle weakness manifests in the patient's early 40s and remains confined to the tibial anterior muscles. Histopathological changes in muscle are compatible with muscular dystrophy, with the exception that rimmed vacuoles are a rather common finding. We performed a genomewide scan, with 279 highly polymorphic Cooperative Human Linkage Center microsatellite markers, on 11 affected individuals of one Finnish TMD family. The only evidence for linkage emerged from markers in a 43-cM region on chromosome 2q. In further linkage analyses, which included three other Finnish TMD families and which used a denser set of markers, a maximum two-point LOD score of 10.14 (recombination fraction of .05) was obtained with marker D2S364. Multipoint likelihood calculations, combined with the haplotype and recombination analyses, restricted the TMD locus to an approximately 1-cM critical chromosomal region without any evidence of heterogeneity. Since all the affecteds share one core haplotype, the dominance of one ancestor mutation is obvious in the Finnish TMD families. The disease locus that was found represents a novel muscular dystrophy locus, providing evidence for the involvement of one additional gene in the distal myopathy group of muscle disorders.